2021
DOI: 10.3389/fpls.2021.640324
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Perennial Ryegrass (Lolium perenne) Vernalization Genes

Abstract: Perennial ryegrass (Lolium perenne) is a temperate grass species commonly used as pasture for livestock. Flowering (heading) of ryegrass impacts metabolizable energy content and seed yield, therefore this trait is important for both farmers and seed producers. In related grass species, the VRN genes (VRN1-3) have been largely implicated in the determination of vernalization response and are responsible for much of the intra-species variation in this trait. Many other important flowering-time regulators have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…Stem elongation marks the maximum growth rate in the growing season (Parsons, 1988), and cv. Trojan (classified as late heading time by Herridge et al (2021)) produced a concentrated flowering in mid‐December, whereas Bv started flowering in early November and continued up until early January (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…Stem elongation marks the maximum growth rate in the growing season (Parsons, 1988), and cv. Trojan (classified as late heading time by Herridge et al (2021)) produced a concentrated flowering in mid‐December, whereas Bv started flowering in early November and continued up until early January (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…families for the cool-season forage grass perennial ryegrass (Lolium perenne L.) (Herridge et al, 2021). The status of these candidate genes in breeding populations of orchardgrass is unknown.…”
Section: Core Ideasmentioning
confidence: 99%
“…In orchardgrass, tremendous variation in HD has been reported (Zhao et al., 2017), and heritabilities have ranged from h 2 = 0.51 to h 2 = 0.89 (Jafari & Naseri, 2007; Majidi et al., 2015). The genetic mechanisms of HD can be separated into vernalization and photoperiod effectors (Fjellheim et al., 2014), with the vernalization response in particular mediated by VRN1, VRN2, and VRN3/FT1 genes (Faure et al., 2007; Herridge et al., 2021; Jack, 2004; Skøt et al., 2007). Many previous studies identified these three VRN genes as quantitative trait loci (QTL) or otherwise candidates for forage grass HD (Herridge et al., 2021; Jokela et al., 2015; Nuñez & Yamada, 2017; Schwartz et al., 2010; Skøt et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allergen Lol p 1 was found in all samples, except CY19. Lol p 1 is the major allergen of the perennial ryegrass (Lolium perenne, Poaceae), which is common in Cyprus and flowers in springtime (Gucel et al, 2013;Herridge et al, 2021), which was the period of sampling. The Bet v 1 type allergens can be found in members of various plant families such as Betulaceae, Fabaceae, and Rosaceae, which are all common in Cyprus.…”
Section: Composition and Community Changes In Fungimentioning
confidence: 99%